Mamíferos continentais ameaçados de extinção do Ceará - Guerra, Thiago Sales Lobo (2023)
Mammals are one of the groups proportionally most threatened with extinction, a reflection of the extinction event driven by anthropogenic actions. Brazil is the most biodiverse country in the world and has 755 known mammal species, of which 183 were specific to the Brazilian Northeast. Of the mammals that occur in the Caatinga, 15 of them are at risk of extinction and 3 are endemic. There are few studies on mammals in the state of Ceará, which has a predominance of the Caatinga biome. Studies on the state's mammals are concentrated on species inventories and there are no state public policies that are exclusively external for the protection of wild fauna. In this context, the fundamental point for establishing effective actions is the preparation of a list of threatened fauna. This document categorizes species into different types of extinction threats: habitat loss and manipulation, hunting, renewable energy. In the Northeast region, only Pernambuco and Bahia published their lists and the absence of this document in other states has consequences from a conservative point of view. In 2018, the Ceará Environment Secretariat (SEMA) began activities to prepare the Red Book of Fauna Threatened with Extinction in Ceará. This process also allows the identification of priority areas for the conservation of mammals in the state of Ceará, a fundamental panorama for the effective targeting of conservation strategies. Therefore, the objective of this work is to identify gaps in knowledge about diversity and occurrence, and estimate the distribution areas of wild mammal species in the State of Ceará as a subsidy for the preparation of evaluation forms for its Red Book of Threatened Fauna, as well as how to determine priority areas for the conservation of these species in the state territory. To this end, a scientometric analysis of publications on the composition of the mammal fauna was carried out, the inventory was updated through the measurement of materials deposited in collections and by partner researchers, and the mammal distribution map was drawn up using the Minimum Convex Polygon – MPC. In total, 130 species of land mammals were identified for the state of Ceará, two of which were categorized as Regionally Extinct (RE) Priodontes maximus and Tapirus terrestris. Most are settings like medium and large earnings and are under some degree of threat at the state level.